A game of Identities: debates over history in Greek Cypriot education. (1st May 2013) - Perikleous, Lukas
This paper discusses the ways in which a battle which lasted over a century between the Hellenocentric and Cyprocentric approaches in Greek Cypriot education manifested itself in debates over history education during the 20th and the 21st century. These were mostly about the version of the past that should be taught to students. The debates over the selection of the story to be taught were essentially disputes over the identity that should be promoted through history education. On one hand the supporters of a Hellenocentric orientation argued in favor of promoting a Greek national identity, while the supporters of a Cyprocentric orientation supported the idea of promoting a Cypriot civic identity common for Greek Cypriots and Turkish Cypriots. The dominance of the Hellenocentric approach during the 20th century is being challenged by the Cyprocentric one at the beginning of the new millennium. At the same time a new disciplinary approach in history education has emerged. Although at the moment this is wrongly associated by many with the Cyprocentric one, it is essentially radically different from both traditional approaches. Although during the last 4 years history education has not been at the centre of attention, political agendas and the current implementation of the New Curriculum 2010 for history education can produce new debates.